Exploring changes in couples' functioning throughout Parkinson's disease - Charlotte Manceau; Émilie Wawrziczny; Émilie Constant; Bérengère Flinois; Kathy Dujardin; Pascal Antoine (British Journal of Health Psychology, 2026)
Abstract Objectives Couples facing Parkinson's disease (PD) deal with continuous adaptation to the numerous challenges PD brings, suggesting an evolving functioning over time, which remains understudied. The present study aimed to provide an integrative understanding of couples' functioning in PD by exploring and identifying distinct patterns of couple functioning and their potential trajectories over the course of PD. Design To overcome common challenges associated with longitudinal approaches, this study uses a qualitative cross‐sectional design, aiming to put into perspective qualitative data collected at three different time points of PD. Methods Forty‐five couples facing PD were interviewed. Data were analysed using Interpretative Phenomenological Analysis, which first enabled us to identify dyadic processes characterizing distinct patterns of couples' functioning. Their evolution was examined, revealing potential trajectories of these patterns. Results Five distinct patterns of dyadic functioning were identified: ‘Coping with the disease, together’, ‘Helping in the shadows’, ‘Avoid the disease or collapse’, ‘Action vs. withdrawal’ and ‘The most total gap between us’. While some couples' functioning tends to remain stable or become more rigid within a single pattern, others may evolve and shift towards another pattern of couple functioning as PD's symptoms change, intensify or are anticipated to worsen. Conclusions This study underscores the need to consider dyadic functioning and its potential evolution in support of couples as early as possible in the course of PD. This study also encourages studies proposing staggered, small‐sample follow‐ups as a viable approach to better and fully capture transitions in couples' functioning in slow‐evolving illnesses like PD.